Letra: A Teacher Training Program Based on the Adoption of Different Roles - Colognesi, Stéphane; Lucchini, Silvia (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
This Note from the Field presents a teacher training program that seeks to support changes by the trained teachers in their own practice. Change in practice is made possible by the teachers’ assuming four successive roles in the training program: Learner, Engineer, Teacher / Observer, Reflective Analyst (LETRA). LETRA has been tested and tried and has shown promising results. The design of the program is presented in this text, step by step. The views of teacher participants are highlighted.